Efeitos de protocolos de exercícios para o assoalho pélvico no tratamento da incontinência urinária de esforço em mulheres - Sebben, Vanessa (2011)
The aim of this study was to verify the effectiveness of a program of exercises for pelvic floor divided in three stages (initial, intermediate and advanced) in the treatment of stress urinary incontinence (SUI) in middle-aged and elderly women. It was accomplished a randomized clinic experiment with 65 women with SUI. They were divided randomly into three groups. The Control group only had evaluative clinic tests. Random Intervention group in addition to evaluative tests had the protocol exercise of pelvic floor and the Standardized Intervention Group besides the evaluative tests held the protocol of exercise respecting the pelvic floor ones for each phase (initial, intermediate and advanced). Both Intervention groups performed 24 practice sessions, during three months and all groups were accompanied after thirty days of the end of the programme of exercises in "follow up". It was used as an instrument for evaluating the Pad Test of 1 hour, the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) and clinical data. The population in case had an average age of 68.6 years old and they have had incontinence for 5.9 years old, 58.5% were hypertensive, 20% diabetic and 58.5% used diuretics. Both groups showed significant improvement in intervention Pad Test and ICIQ-SF when compared to Control group, but there was no significant difference in Pad Test and ICIQ-SF between Intervention groups. We observed in our study that pelvic floor exercises are effective in reducing and/or cure of SUI